Why Some Faces won't be Remembered: Brain Potentials Illuminate Successful Versus Unsuccessful Encoding for Same-Race and Other-Race Faces - Lucas, Heather D.; Chiao, Joan Y.; Paller, Ken A. (Frontiers in Human Neuroscience, 2011)
Memory is often less accurate for faces from another racial group than for faces from one's own racial group. The mechanisms underlying this phenomenon are a topic of active debate. Contemporary theories invoke factors such as inferior expertise with faces from other racial groups and an encoding emphasis on race-specifying information. We investigated neural mechanisms of this memory bias by recording event-related potentials while participants attempted to memorize same-race and other-race faces. Brain potentials at encoding were compared as a function of successful versus unsuccessful recognition on a subsequent memory test. Late positive amplitudes predicted subsequent memory for same-race faces and, to a lesser extent, for other-race faces. By contrast, the amplitudes of earlier frontocentral N200 potentials and occipito-temporal P2 potentials were larger for later-remembered relative to later-forgotten other-race faces. Furthermore, N200 and P2 amplitudes were larger for other-race faces with features considered atypical of that race relative to faces that were race-stereotypical (according to a consensus from a large group of other participants). In keeping with previous reports, we infer that these earlier potentials index the processing of unique or individuating facial information, which is key to remembering a face. Individuation may tend to be uniformly high for same-race faces but lower and less reliable for other-race faces. Individuation may also be more readily applied for other-race faces that appear less stereotypical. These electrophysiological measures thus provide novel evidence that poorer memory for other-race faces stems from encoding that is inadequate because it fails to emphasize individuating information.